Dexmedetomidine reduces in-hospital mortality in aneurysmal subarachnoid hemorrhage patients by modulating three key genes and inflammatory pathways: insights from clinical and bioinformatics analyses - Zhi-ang Li; Hong-cai Wang; Xue-wei Zhang; Li-hong Hu (Frontiers in Neurology)
BackgroundAneurysmal subarachnoid hemorrhage (aSAH) is a cerebrovascular disease with high mortality. Dexmedetomidine has a neuroprotective effect. This study aimed to explore the clinical and molecular association between dexmedetomidine and in-hospital mortality of aSAH.MethodsPatients with aSAH in the MIMIC-IV database were included and divided into non-in-hospital mortality and in-hospital mortality groups. Two machine learning algorithms random forest (RF) and XGBoost ranked treatment variables, and overlapping variables between these two algorithms were selected to evaluate their prognosis value for aSAH. Bioinformatics approaches, including DEG analysis, pathway enrichment, immune infiltration, and GSEA, explored potential mechanisms. Molecular docking assessed interactions between dexmedetomidine and identified hub genes.ResultsA total of 505 individuals with aSAH were included in this study, with 114 dying in-hospital. Patients in the in-hospital mortality group exhibited older age, higher SAPS II scores, and altered physiological parameters. Dexmedetomidine was the most influential treatment variable, significantly associated with reduced in-hospital mortality. Bioinformatics identified three hub genes (MyD88, AR, AREG) related to aSAH and dexmedetomidine. These hub genes showed promising diagnostic accuracy in aSAH, with all AUC values over 0.67. Immune infiltration and GSEA highlighted the involvement of hub genes in inflammation and immune regulation. Molecular docking revealed AR as a direct target of dexmedetomidine (binding energy = −5.68 kcal/mol).ConclusionDexmedetomidine is correlated with reduced in-hospital mortality in aSAH, potentially by regulating AR and immune pathways. These findings highlight AR as a promising therapeutic target of dexmedetomidine for aSAH management.